Adapting therapy for a new world: storytelling therapy in EVA Park. Issue 5 (4th May 2021) - Carragher, Marcella; Steel, Gillian; Talbot, Richard; Devane, Niamh; Rose, Miranda L.; Marshall, Jane
ABSTRACT: Background: Storytelling is fundamental to human communication yet is under-represented in aphasia therapy research and clinical practice. Access to care may be one obstacle; in the broader healthcare context, remote modes of treatment delivery can increase individuals' access to care. EVA Park is a highly novel, online platform designed with people with aphasia that has shown capacity to improve aspects of language and communication. Aims: This study explored whether it is feasible to deliver a storytelling intervention in EVA Park and whether therapy brought about improvements in the content and organisation of their narratives. Changes in functional communication and technology use were also examined. Methods and procedures: In a pilot feasibility study, three individuals with aphasia were recruited in the UK and Australia. Over five weeks, participants received 20 hours of therapy in EVA Park, consisting of three weekly sessions with a speech therapist and one weekly session in which the participant told the story to a volunteer who was blinded to the content of their story. A repeated-measures, case series design was used to evaluate therapy. The primary measure assessed the content of narratives elicited by novel video stimuli twice before and twice after therapy. Secondary measures investigated structural features of the video narratives and of personal narratives. Functional communication was assessed with the Communication Activities of Daily Living assessment, and technology use was probed via a Technology Screen. Outcomes and results: Delivery of storytelling therapy via EVA Park was feasible; technology challenges arose and were resolved using multiple strategies. Following therapy, participants' storytelling improved in content, with a large effect size for the group, and in structure. Generalisation to personal narratives was not observed. Some improvements were seen in functional communication. Conclusions: Storytelling therapy delivered via an online platform is feasible and may improve the content and organisation of participants' storytelling, with some evidence of generalisation to functional communication.